2011
DOI: 10.1017/s1743921312004802
|View full text |Cite
|
Sign up to set email alerts
|

Interplanetary conditions: lessons from this minimum

Abstract: Abstract.Interplanetary conditions during the Cycle 23-24 minimum have attracted attention because they are noticeably different than those during other minima of the space age, exhibiting more solar wind stream interaction structures in addition to reduced mass fluxes and low magnetic field strengths. In this study we consider the differences in the solar wind source regions by applying Potential Field Source Surface models of the coronal magnetic field. In particular, we consider the large scale coronal fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Following the comparison of EUV levels between minimum periods, the superposed epoch analysis (Figure 3) clearly showed that the last two minima had lower EUV radiation levels than did the first two, together with a longer duration. This was already observed by several authors, especially in the case of min23-24 (Luhmann et al, 2012). In addition, each minimum was lower than the previous one, except MgII for the first two periods.…”
Section: Discussionsupporting
confidence: 79%
“…Following the comparison of EUV levels between minimum periods, the superposed epoch analysis (Figure 3) clearly showed that the last two minima had lower EUV radiation levels than did the first two, together with a longer duration. This was already observed by several authors, especially in the case of min23-24 (Luhmann et al, 2012). In addition, each minimum was lower than the previous one, except MgII for the first two periods.…”
Section: Discussionsupporting
confidence: 79%
“…The number of shocks driven by SI was higher during the studied time interval, and this is related to the unusual configuration of the magnetic field in the solar corona during the extended minimum, which showed significant coronal holes at medium and low latitudes [ Luhmann et al ., ]. As the solar cycle evolves, the number of shocks driven by stream interaction does not vary much with 38 shocks observed by STEREO in the interval 2011–2012 (Blanco‐Cano et al, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 95%